(untitled) (KULT_online, 2012)
How could the interventionist potential of cultural studies and poststructuralist approaches to critique and resistance cross-fertilize? How could the sophisticated theories of philosophers like Michel Foucault and Judith Butler be translated into concrete practices? In his partly cumulative PhD thesis Performative Kritik. Eine philosophische Intervention in den Begriffsapparat der Cultural Studies (Performative Critique: A Philosophical Intervention into the Terminology of Cultural Studies). Sebastian Nestler considers these questions and suggests including the concept of ’performative critique’ (developed in accordance with Foucault and Butler) in the conceptual framework of cultural studies. The exemplary analyses of movies and TV series are, then, supposed to transfer the theory into a concrete practice of analysis, which Nestler himself wants to be understood as a particular form of intervention in itself. The book does not meet its own ambitious aspirations. Yet, it may very well serve as solid theoretical ground-work for a ’performative critique’ that has yet to be developed.